Regenerating Craniofacial Dental Defects With Calcium Phosphate Cement Scaffolds: Current Status and Innovative Scope Review - Alsahafi, Rashed A.; Mitwalli, Heba Ahmed; Balhaddad, Abdulrahman A.; Weir, Michael D.; Xu, Hockin H. K.; Melo, Mary Anne S. (Frontiers in Dental Medicine, 2021)
The management and treatment of dental and craniofacial injuries have continued to evolve throughout the last several decades. Limitations with autograft, allograft, and synthetics created the need for more advanced approaches in tissue engineering. Calcium phosphate cements (CPC) are frequently used to repair bone defects. Since their discovery in the 1980s, extensive research has been conducted to improve their properties, and emerging evidence supports their increased application in bone tissue engineering. This review focuses on the up-to-date performance of calcium phosphate cement (CPC) scaffolds and upcoming promising dental and craniofacial bone regeneration strategies. First, we summarized the barriers encountered in CPC scaffold development. Second, we compiled the most up to date in vitro and in vivo literature. Then, we conducted a systematic search of scientific articles in MEDLINE and EMBASE to screen the related studies. Lastly, we revealed the current developments to effectively design CPC scaffolds and track the enhanced viability and therapeutic efficacy to overcome the current limitations and upcoming perspectives. Finally, we presented a timely and opportune review article focusing on the significant potential of CPC scaffolds for dental and craniofacial bone regeneration, which will be discussed thoroughly. CPC offers multiple capabilities that may be considered towards the oral defects, expecting a future outlook in nanotechnology design and performance.